6‐Chloropurine Ribonucleosides from Chloropyrimidines: One‐Pot Synthesis. Issue 1 (13th August 2018) - Zelli, Renaud; Zeinyeh, Waël; Décout, Jean‐Luc
Abstract: A one‐pot glycosylation and cyclization procedure is described for the synthesis of 6‐chloropurine ribonucleosides from chloropyrimidines. From such a procedure and modification of the obtained chloropurine ribonucleosides, many drug candidates or molecular tools for biological study designed from their similarity to naturally occurring nucleosides could be obtained. The synthesis begins by preparation of several amidinoaminochloropyrimidines as precursors for the one‐pot procedure. Then, by adding trimethylsilyl trifluoromethanesulfonate (TMSOTf) to a mixture of a pyrimidine and 1‐ O ‐acetyl‐2, 3, 5‐tri‐ O ‐benzoyl‐β‐D ‐ribose, different 6‐chloropurine ribonucleosides are obtained. This methodology allows the straightforward introduction of an alkyl substituent at position 8 of purine ribonucleosides, which then can be functionalized at positions 2 and 6. © 2018 by John Wiley & Sons, Inc.